Trend of Development of Ottoman Caliphate (716-804 After Hijrah) from warriorship to Governance - Ahmad Fallahzadeh (تاریخ اسلام)
Ottoman caliphate as the last Islamic Empire has passed various stages in time of development.The increasing development of this government from leadership, government and caliphate shows several phases of transferring the political-military thought of authority in itself. This dynasty’s achieving a political-military organization in a historical phase is due to the failure of Saljuqids in Rome, the geography of conquests and possessions, and their imagination about victories. Meanwhile, the role of religious structure of Anatoly region, following of Turkism in this area, warriorship of the Turkish and the process of collapse of Byzantine Empire should not be denied. Analyzing and describing the data, the present article is to investigate the tribal structure of Turkish , Ottomans’ inheriting from Saljuqids, belief discourses in ottoman conquests , ottomans’ taking advantage of Safavid thoughts, selecting Hanafi jurisprudence and the political role of Turkish language and to show that ottoman caliphate has passed four phases in the first century of its life from the beginning of Ottoman’s possessions (716) to Fetrat resulting from the Timor’s victory and conquering Bayazid (804), from the warriorship to the development of government